A one-on-one approach to start institutionalising experience capitalization - Ayebare, Prudence (Technical Centre for Agricultural and Rural Cooperation, 2019)
To encourage the adoption of the experience capitalization approach within the Uganda National Farmers Federation, those who had joined the CTA training workshops opted to share information and explain the main concepts and the steps involved to all team members through tailored one-on-one sessions. Through such meetings, the trained staff were able to convey the importance of the approach and demonstrate how it could meet the varying needs of the different departments.